Confronting sustainable intensification with uncertainty and extreme values on smallholder tropical farms - Knoke, Thomas; Gosling, Elizabeth; Reith, Esther; Gerique, Andrés; Pohle, Perdita; Valle Carrion, Liz; Ochoa Moreno, Wilman Santiago; Castro, Luz Maria; Calvas, Baltazar; Hildebrandt, Patrick; Doellerer, Martin; Bastit, Felix; et al. (SUSTAIN SCI, 2022)
Sustainable intensification of agricultural lands might reconcile the conservation of tropical forest with food production, but in-depth assessments considering uncertainty and extreme values are missing. Uncertainty prohibits mapping probabilities to potential future states or ranking these states in terms of their likelihood. This in turn hampers the assessment of possible decision outcomes. Here, we use simulations to investigate how uncertainty may influence the social acceptability of alternative land-use strategies to halt tropical deforestation (including sustainable intensification), based on indicators representing farmer satisfaction. The results show how extreme values (worst values) for indicators of farmer satisfaction may undermine the adoption of sustainable intensification. We demonstrate that a pure forest conservation strategy leads to lower food production, but outperforms a sustainable intensification strategy that maintains food security. Pure forest conservation performed better, i.e., could secure higher farmer satisfaction, than sustainable intensification across a range of indicator groups. This suggests strong barriers to achieving sustainable intensification. Using agricultural subsidies breaks the dominance of pure forest conservation by enhancing the economic returns of sustainable intensification. We discuss the importance of access to labor and farmers’ preferences for the use of already cleared lands, which achieved the worst values under sustainable intensification and conclude that any assessment of land-use strategies requires careful consideration of uncertainty and extreme values.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Agricultural intensification; Farmer preferences; Land allocation; Multiple objective robust optimization; Off-farm income; Tropical deforestation